Implementing Differentiated Learning through Nusantara Cultural Coloring Activities in Grade IV Integrated Natural and Social Sciences - Myrtawati Myrtawati; Heri Maria Zulfiati; Insanul Qisti Barriyah; Dinar Westri Andini; Akbar Al Masjid (Journal of General Education and Humanities, 2026)
This study aims to describe the implementation of differentiated learning through Nusantara cultural coloring activities in science learning (IPAS) in grade IV of elementary school, and to explore teachers' perceptions of how these activities relate to students' engagement, motivation, conceptual understanding, creativity, concentration, and participation. This study used a qualitative, single-case design, conducted at SD Negeri 01 Gumawang, involving one fourth-grade class of [X] students and one classroom teacher as the primary informant and facilitator of the learning activities. Data were collected over [X weeks/sessions] through [X] non-participatory classroom observations, one in-depth interview with the teacher, and documentation of student coloring work. Data were analyzed using thematic analysis, involving data reduction, categorization, and interpretation of interview and observation findings. The findings indicate that differentiation was applied primarily at the process and product levels, as students were given flexibility to choose colors, coloring techniques, and the level of detail in completing their assignments. At the same time, content and learning objectives remained the same for all students. The teacher reported adjusting support based on observed differences in student readiness, providing additional guidance and color examples for students who needed more assistance, and encouraging more advanced students to add cultural details or ornaments. Based on the teacher's observations and interview accounts, the coloring activities were perceived to contribute to a more enjoyable, concrete, and contextual learning environment, and were associated with increased student engagement, motivation, and interest in the cultural material. The teacher also reported observing improvements in students' attentiveness, participation, and confidence during the activity, along with signs of stronger recall of cultural symbols and concepts; however, these outcomes were not measured through tests, rubrics, or standardized observation instruments, and should be interpreted as the teacher's professional perception rather than objectively verified learning outcomes. As a single-classroom case study, these findings offer contextual insight into one teacher's practice and should not be generalized beyond this setting without further research involving multiple classrooms and more systematic measurement tools.